2017
DOI: 10.14419/ijans.v6i1.7415
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of insomnia and its associated factors among rural elderly: a community based study

Abstract: Background: Insomnia is a common problem among older adults and can lead to several complications affecting the quality of life of elderly people. Aim: To estimate the prevalence of insomnia and its associated factors among community-dwelling elderly. Study design: This is a cross-sectional descriptive study carried out on 1059 elderly living in three villages affiliated to Mansoura District, Egypt. Data collected during an interview included: socio-demographic and clinical features, habits before sleeping, en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 30 publications
1
15
0
2
Order By: Relevance
“…Our study showed that 71.1% of respondents had insomnia which is in line with other studies in India (Ahmad et al, ), Egypt (El‐Gilany, Saleh, Mohamed, & Elsayed, ), Korea (Jeon & Choi‐Kwon, ) and Nepal (Shrestha et al, ). On contrary, some other studies in the USA (George et al, ; Mendoza‐Meléndez et al, ; Miner et al, ), Singapore (Sagayadevan et al, ), Iran (Hosseini et al, ), South Korea (Kim et al, ) and China (Luo et al, ; Tsou, ) have shown lower prevalence than the current study.…”
Section: Discussionsupporting
confidence: 92%
“…Our study showed that 71.1% of respondents had insomnia which is in line with other studies in India (Ahmad et al, ), Egypt (El‐Gilany, Saleh, Mohamed, & Elsayed, ), Korea (Jeon & Choi‐Kwon, ) and Nepal (Shrestha et al, ). On contrary, some other studies in the USA (George et al, ; Mendoza‐Meléndez et al, ; Miner et al, ), Singapore (Sagayadevan et al, ), Iran (Hosseini et al, ), South Korea (Kim et al, ) and China (Luo et al, ; Tsou, ) have shown lower prevalence than the current study.…”
Section: Discussionsupporting
confidence: 92%
“…Also, the variation cannot be attributed purely to differences between ethnic groups, rural and non-rural population, and nursing home and non-nursing home data. A relatively low percentage (15%) of elders has insomnia in the Domkhar valley in India's Ladakh Foley et al 55 23-34% USA Ohayon 56 30% France Maggi et al 57 45% Italy Chiu et al 58 38.2% Hong Kong (Chinese population) Babar et al 59 32.6% Hawaii (Japanese Americans) Kim et al 60 26.4% Japan Pallesen et al 61 38.6% Norway Schubert et al 62 26.4% USA Sukying et al 63 46.3% Thailand Su et al 64 6% Taiwan Yu et al 65 10.4% China Bonanni et al 66 44.2% Italy López-Torres et al 67 36.1% Spain Kim et al 68 29.2% South Korea Li et al 69 49.7% China (rural) Tsou 70 41% Taiwan Ayoub et al 71 33.4% Egypt Ford et al 72 21.3% USA Sagayadevan et al 73 13.7% Singapore (Chinese, Malay, Indian descent) Sakamoto et al 74 15.2% Ladakh, India El-Gilany et al 75 62.1% Egypt (rural) Eser et al 76 60.9% Turkey (nursing home) Makhlouf et al 77 33.4% Egypt (geriatric home) Gambhir et al 78 32% India (hospital) Ogunbode et al 80 27.5% Nigeria (geriatric centre) region, which is at a high altitude of 2900-4200 m. 74 According to some reports, there is a higher prevalence of insomnia in the aged in nursing homes and rural areas. 69,75,76 However, other studies have found no differences in the insomnia patterns of elders in nursing homes and in other homes.…”
Section: Insomnia In the Elderlymentioning
confidence: 99%
“…Insomnia is one of the most common sleeping disorders . In previous studies in other countries, the prevalence of insomnia, which was defined as a chronic sleeping disorder, ranged from 32.4% to 67.24% among the population aged 65 years old and older . In the first and only community‐based study performed by Benbir et al ., the prevalence of insomnia was found to be 13.9% among 418 adults aged 65 years and older in Turkey .…”
Section: Introductionmentioning
confidence: 98%
“…The prevalence of insomnia is significantly affected by various sociodemographic and medical factors such as sex, age, marital status, income level, education level, employment status, and somatic or psychiatric conditions . It is important to determine the sociodemographic and medical factors that are associated with insomnia on distinct country samples in order to decrease negative outcomes …”
Section: Introductionmentioning
confidence: 99%